Wizerunek malowany frazeologią (na przykładzie języka ukraińskiego): A picture painted in phraseology (on the example of Ukrainian language) - Nowakowska-Kempna, Iwona (Przegląd Wschodnioeuropejski, 2020)
The metaphorical title A Picture Painted in Phraseology is meant to refer to the created picture of EMOTIONS, though the material used here is not paint, but the phrasemes employed in the description of EMOTIONS. By default, the phraseology of EMOTIONS is destined to create their picture. This picture is usually conventional since phrasemes are linguistically well entrenched and conventional. The correlation between the appearance of an experiencer, the picture of his or her face and behaviour, and his or her emotional state becomes a basis for the creation of numerous phrasemes, which are indicative of this correlation. The picture exists both in language and cognition. Phrasemes produce a specific picture of an experiencer who undergoes an emotion in such a way that one may argue that a picture is actually painted in phraseology. The final result is the picture of FACE and BODY, displaying joy, sadness, fear or surprise, which is exclusively characteristic of a particular emotion